Innovation below the surface: development of a canine underwater search training device for submerged scent detection - Bunker, Paul; Brewster, Christina (Frontiers in Veterinary Science, 2026)
The effective detection of targets in aquatic environments, particularly underwater, poses a significant challenge for environmental and conservation monitoring and response. Canines are used in a detection role to search for human cadavers, whale scat, invasive fish, and spilled oil. The use of canines for underwater detection is limited by our imagination, and in some cases, the ability to train the canines using the target samples. A significant challenge in training a canine for underwater detection, such as oil, is that the target (oil) cannot be placed in water environments, which could contaminate the water source. This paper describes the design, development, training protocols, and validation of a Canine Underwater Search Training Device (CUSTD), which is a novel, remotely operated system that facilitates the training of canines to detect underwater targets safely and, relatedly, without the need to place training materials directly in the water source. The device allows for trainers and handlers to deliver target odors from the front of a boat, therefore conditioning a detection canine to search from the front of a boat and to give a response (indication) when the target odor is detected. In October of 2024, a research study assessed the ability of canines to detect petroleum-based compounds underwater in controlled field conditions. Canines initially were trained to recognize the volatile organic compounds (VOCs) associated with crude oil underwater from a boat using the CUSTD. The innovation of the device provided the ability to expose the canine to target VOCs from the front of a boat without requiring oil to be placed within the water source. The methodology has wider potential applications, including environmental monitoring, oil spill response, search and recovery, and marine biology research. The CUSTD provides a versatile and ethical platform for advancing both scientific study and operational canine deployment in underwater detection disciplines.